Символ в социологической теории - Огаренко, Т.; Скидин, Л. (Iнститут соціології НАН України, 2009)
The concept-category apparatus of symbols and symbolic interaction is analyzed in this article from the sociological point of view. It is emphasized, that the symbols in the social sciences can be not only the subject matter of special research, but its means that is its methodology as well. Symbol is examined as: social phenomenon, resource of social interaction, adaptive resource, mechanism of selfpresentation and the variety of "social capital". Besides, the authors analyse the sociological problem of uncertainty of concrete contents of the object designated by certain symbol. The position, that the historical evolution is first of all the evolution of forms of symbolic presentation and selfpresentation finds its further confirmation. The systematic review of symbolic interaction within the framework of groups of individual's nearest surroundings, conformities of perception of communicative complexes, mechanisms of self-determination of personality is presented here as well. Specificity of accentuation of symbols on resemblance, similarity, identity and sometimes on difference, exception, peculiarity, unidentity is also revealed in the article.